Psychological Analysis of Audio and Video Materials Obtained during Police Operations: Organizational and Methodical Aspects - T. N. Sekerazh (Теория и практика судебной экспертизы)
The article addresses typical expert situations arising in the psychological analysis of video materials from police operations. The author demonstrates that to solve the emerging issues, an expert needs specialized knowledge, especially in forensic psychology and linguistics. Furthermore, the eﬃciency of solving expert tasks in examining video materials of police operations for various categories of detected oﬀenses depends on some organizational and methodological factors. The author also reviews typical expert errors associated with an incorrect recognition of the object of research, the outline of expert tasks, the choice of methods, and the limitations in the use of case materials by experts.